Study of the effect of chalcopyrite and pyrite minerals on the oxidation of copper sulfide concentrate - G, Gereltuya.; B, Maralmaa.; D, Erdenechimeg. (Mongolian Journal of Engineering and Applied Sciences, 2020)
Changes in the weight of copper concentrate from oxidation and a decrease in copper content create economic losses. Mining plants having problems with increasing overall weight of the copper concentrate and reduction of the copper composition after a certain period of transport and handling. Trivalent iron, one of the main oxidizing factors of the copper concentrate, is a strong oxidizer that oxidized copper sulfide minerals as well as other minerals in the concentrate, which is formed by the oxidation of pyrite. Generally, mass change can occur during electron transition and phase transfer. Therefore, the chemical mechanism, oxidation process, and content alteration of the main components in copper concentrate were studied in this study in order to solve and define those problems. To study the real condition of the copper concentrate oxidation, the oxidation process of the copper concentrate was studied under 3 conditions such as in the shadow, in the sun, and the storage. Mongolian National Standard and International standards (MNS2078:1984, ISO 10258:2018) and XRD, AAS, ICP analysis were used to study the main components of the copper concentrate. By the study on the oxidation of copper concentrate at the mine site, copper was decreased by 0.77-0.85%, and iron was reduced by 0.30-0.64%. As a result of the oxidation study of concentrate that is kept in the mining site, temperature, relative humidity, and pH were highly correlated with concentrate oxidation.